River Mitigation as a Form of Elderly-Nature Interaction in Densely Populated Settlement in Yogyakarta - Muhammad Aldi Rahmatul Hakim; Diananta Pramitasari (Jurnal Kawistara, 2021)
High population density has been associated with disease susceptibility. To address this problem many suggest that the negative effects of population density can be reduced by interacting with nature as a restorative activity. This study aims to determine how the elderly in the residential areas on the banks of the Winongo river, Ngampilan District, Yogyakarta City with high population density interact with nature in the riverside environment, and what form of space is needed. This study uses a deductive exploratory method with elderly respondents who are active on the riverbank. The results showed that the riverside space which is used as a space for interaction between the elderly and nature is a room with sitting facilities, walls that are not closed, and shade that is not too tight. Interactions with nature that occur can be in the form of physical restoration, recreation, domestic, and mitigation activities. The activity of seeing water levels as flood mitigation is the most dominant form. Physical limitations make elderly people more aware of disasters along the riverbanks. A space that makes it easier for the elderly to do disaster anticipation activities needs to be prepared for long-term planning.